Um silêncio eloquente? O que a ausência do Direito da criança e do adolescente no Exame Nacional da Magistratura nos diz? - Oliveira, Heitor Moreira De [UNESP]; Naspolini, Samyra Haydêe Dal Farra (Programa de Pós-Graduação em Direito da Universidade Federal de Santa Catarina, 2024)
The CNJ Resolution No. 531/2023 establishes the National Judiciary Exam as a prerequisite for applying to a judicial position, consisting of an objective test with fifty questions divided into eight thematic blocks. Children’s and Adolescents’ Rights do not appear among the subdivisions of knowledge selected to compose the groups of questions for the exam. This article aims to investigate what this absence it means in the broader context of juridical education in Brazil. To this end, we conducted a review of bibliographic texts that examine the historical evolution of this area of Law, as well as sources that evaluate the formatting of the curricular matrix of legal courses in Brazil. Additionally, a survey of empirical data was carried out on the presence or absence of Children’s and Adolescents’ Rights in the curriculum of Law courses in the twenty best-evaluated universities in the RUF 2023 ranking. The results collected in the research showed that the absence of this area of legal knowledge in the National Exam reflects the undisguised negligence given to the discipline in the academic and professional training of students who will become judges and goes back to the historical evolution of the profile of childhood and youth magistrates in Brazil.

A Resolução CNJ nº 531/2023 instituiu o Exame Nacional da Magistratura, como pré-requisito para inscrição nos concursos da magistratura, consistente em uma prova objetiva com cinquenta questões divididas em oito blocos temáticos. O Direito da Criança e do Adolescente não figura dentre os ramos do conhecimento selecionados para compor os grupos de questões do Exame. O presente artigo tem por objetivo investigar o que essa ausência significa no contexto mais amplo do ensino jurídico no Brasil. Para tanto, buscou-se realizar uma revisão de textos bibliográficos que examinam a evolução histórica desse ramo do Direito, bem como de fontes que avaliam a formatação da matriz curricular de cursos jurídicos no Brasil. Além disso, foi feito um levantamento de dados empíricos sobre a presença ou não do Direito da Criança e do Adolescente no currículo dos cursos de Direito nas vinte faculdades mais bem avaliadas no RUF 2023. Os resultados colhidos na pesquisa evidenciaram que a ausência desse ramo do conhecimento jurídico no Exame Nacional reflete a indisfarçável negligência dada à disciplina na formação acadêmica e profissional dos estudantes que se tornarão juízes e juízas e remonta à evolução histórica do perfil dos magistrados da infância e da juventude no Brasil.
An eloquent silence? What do the absence of The right of children and adolescents in The razilian judiciary exam tell us?
Keywords: National Judiciary Exam; Children’s and Adolescents’ Rights; Juridical education; Curricular guidelines; Exame Nacional da Magistratura; Direito da Criança e do Adolescente; Ensino jurídico; Diretrizes curriculares.